The acute effects of varying whole body vibration exposure on the jump height of club volleyball players - Naidoo, R.; Dlamini, K. P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Whole body vibration (WBV) has demonstrated rapid improvement to muscle strength or power when being vibrated on a platform. However, WBV studies have utilised sedentary individuals as participants and limited on athletes whom strength and power are their primary development in sport. There is an opportunity for South African athletes to improve their power output during game time using whole body vibration or as warm up protocol before games. The objective of this study was to measure the acute effects of varying high and low frequencies [0, 30, 35, 40, and 50 Hz] set at high and low displacements of WBV for 30 seconds on the countermovement jump performance in club volleyball players. Methods: A single-blinded repeated-measures crossover study design was conducted. Club volleyball players (n=30), 27 males (age, 25.33 ± 5.86 years; height, 1.83 ± 0.73 m; weight, 84.06 ± 13.23 kg) completed countermovement jumps (CMJs) of maximal volition to assess peak power pre and post (immediately) randomised WBV stimuli set at varying frequency (0, 30, 35, 40, and 50 Hz), displacement (2-4 vs. 4-6 mm), and duration (30 seconds) combinations. Results: Significant main effects were found for power (pre-to-post WBV, p 0.048), with repeated measures analysis of variance (paired sample test) emphasising that there was significant mean improvement of 9.4% in CMJ as a result of WVB at 35Hz but no significant change at other frequencies. Therefore, this study demonstrates that for athletic trained men, an acute 30-second bout of vertical WBV at 35Hz and 4-6mm peak-topeak displacement significantly improves explosive jumping performance in comparison to other frequencies. Conclusion: Acute vertical WBV for 30 seconds at 35Hz may be utilised as part of the warm up session to enhance explosive power in volleyball players; however, the exact mechanisms for improvements still need further well controlled investigations on chronic WBV training utilising strength/ power trained athletes.